Pembrolizumab‐induced pancytopenia in a patient with squamous cell lung cancer. Issue 9 (7th August 2020) - Ueki, Yuriko; Suzuki, Manabu; Horikawa, Yuriko; Watanabe, Hiromu; Yamaguchi, Yoh; Morita, Chie; Tsukada, Akinari; Takumida, Hiroshi; Kusaba, Yusaku; Katsuno, Takashi; Tsujimoto, Yoshie; Sakamoto, Keita; et al.
Abstract: Immune checkpoint inhibitors (ICIs) are reportedly effective against many kinds of neoplasm, but may be responsible for several kinds of immune‐related adverse events (irAEs). Among these irAEs, the incidence of myelosuppression due to ICIs is relatively low. Corticosteroids are needed to control most cases of myelosuppression. Here, we report an 88‐year‐old woman with squamous cell lung cancer who was administered pembrolizumab. After five cycles of pembrolizumab, she developed severe pancytopenia. The pancytopenia improved under observation without steroid administration after cessation of pembrolizumab. During recovery from this irAE, the patient also maintained long‐term antitumor efficacy. Key points: Significant findings of the study: There are several kinds of immune‐related adverse events. We encountered a case of pembrolizumab‐induced pancytopenia with squamous cell lung cancer. What this study adds: Corticosteroids are needed to control most cases of myelosuppression induced by ICIs, but pancytopenia induced by pembrolizumab in our case improved without steroids. Abstract : An 88‐year‐old woman with squamous cell lung cancer was administered pembrolizumab. After 5 cycles of pembrolizumab, she developed severe pancytopenia. Pancytopenia improved under observation without steroid administration after cessation of pembrolizumab. During recovery from this irAE, the patient also maintained long‐term anti‐tumor efficacy.